Blood Congestion Can Be Rescued by Hemodilution in a Random-Pattern Skin Flap. Issue 2 (February 2017) - Kanayama, Koji; Mineda, Kazuhide; Mashiko, Takanobu; Wu, Szu-Hsien; Feng, Jingwei; Kinoshita, Kahori; Sunaga, Ataru; Yoshimura, Kotaro
Abstract : Background: There is no standard method to ensure survival of random-pattern skin flaps. The authors developed a rat anemia model to observe survival of random-pattern skin flaps after blood transfusion and hemodilution. Methods: Anemia was induced by withdrawal of 35 percent blood volume followed by compensation with the same amount of blood (blood transfusion model) or plasma equivalent (normovolemic hemodilution). Control rats were subjected to a sham procedure. Subsequently, a random-pattern skin flap (1.5 × 6 cm) was elevated on the back of each rat. Physiologic assessments of flap vascularity/viability were performed using laser Doppler spectrophotometry before and after flap elevation. Results: The normovolemic hemodilution group showed anemia (hemoglobin, 9.5 ± 0.8 g/dl) but less flow occlusion and greater flap survival (72.8 ± 8.6 percent) compared with control (57.4 ± 9.6 percent; p < 0.01) and blood transfusion (62.1 ± 6.5 percent; p < 0.089) groups. In control and blood transfusion groups but not the normovolemic hemodilution group, blood flow was decreased and relative quantity of hemoglobin was increased toward the flap tip, indicating congestion. In control and blood transfusion groups, blood flow and tissue oxygen saturation dropped after flap elevation, but recovered by day 7; congestion gradually improved by day 7. Conclusions: The authors determined that congestion promoted necrosis and hemodilution reduced microcirculatory occlusion and increased blood flow and oxygenation in skin flaps. It was suggested that perioperative hemodilution is superior to blood transfusion in any flap operations unless there is a critical systemic need for blood transfusion. Abstract : Supplemental Digital Content is available in the text.